2021
DOI: 10.1186/s41155-021-00179-8
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity and experience of undergraduate students: an analysis of semantic networks

Abstract: Work experiences during undergraduate studies can be remarkable in the journey of undergraduate students. The objective of this study was to assess, by analyzing semantic networks, the role of work experiences in the meanings those individuals attribute to professional identity. The sample consisted of 2291 students (60% women) divided into three groups: do not work, work in a field related to their course, work in a field not related to their course. The semantic networks of these groups were composed of word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This may be because most students believe expertise and sporting techniques, rather than the in-person experience and internalization of being a teacher, hold the key to occupational commitment. Nonetheless, the internship is instrumental in cultivating teachers' occupational commitment among student teachers, according to multiple studies [22], consistent with what we found. An internship allows trainee teachers to deal with an actual teaching scenario that requires interaction with students, instructors, and the inner self [23], and positive communication helps shape a professional identity [24].…”
Section: Discussionsupporting
confidence: 90%
“…This may be because most students believe expertise and sporting techniques, rather than the in-person experience and internalization of being a teacher, hold the key to occupational commitment. Nonetheless, the internship is instrumental in cultivating teachers' occupational commitment among student teachers, according to multiple studies [22], consistent with what we found. An internship allows trainee teachers to deal with an actual teaching scenario that requires interaction with students, instructors, and the inner self [23], and positive communication helps shape a professional identity [24].…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, significantly higher median professional identity score was observed among HCP as compared to HPS. Research suggests that skills and experience are important factors that have been linked directly to professional identity of healthcare practitioners, which can explain the higher level of professional identity reported among HCP included in our study [3,4,6]. Most healthcare practitioners are expected to have high level of professional identity that is somewhat influenced by their experience.…”
Section: Discussionmentioning
confidence: 77%
“…It has been noted that professional identity develops continuously, starting from experiences gained informally in life and formally in classrooms. These experiences continue to evolve into the work life of individuals that can be influenced by a number of factors including skills and knowledge [3][4][5][6]. Research has shown that all educational experiences outside of the classroom can influence students' level of professional identity [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The professional identities of a student and a specialist are two different phenomena. During the professional training phase, only the prerequisites for professional identity are laid, the formation and further development of which take place after the initial adaptation of the young specialist during more intensive professional activities (Baking, Ibarra, & Mukminin, 2023;Carvalho, De Amorim-Ribeiro, Do Vale Cunha, & Mourão, 2021;Phillips, Dzidic, & Castell, 2022). Thus, professional identity is a sense of independent, conscious ownership of the work performed.…”
Section: The Place Of Professional Identity In the Structure Of Profe...mentioning
confidence: 99%